Social media use, loneliness and emotional distress among young people in Europe - Bego\~na Cabeza Martínez; Beatrice D'Hombres; Matija Kovacic (Global Labor Organization (GLO), 2025)
The rapid rise of social media has transformed communication and raised concerns about its societal impact, particularly on mental health and well-being. Using data from a novel EU-wide survey, this study investigates the association between social media usage, loneliness, and emotional distress among young people across 27 European member states. We find that intensive use of social networking sites correlates positively with loneliness and emotional distress, whereas excess use of messaging tools plays a very limited role. These findings are robust to alternative measures of loneliness and emotional distress and to a variety of model specifications. Young adults who either grew up with smartphones during their teenage years or their twenties are particularly vulnerable to excessive use of social network sites. Further analysis suggests that the harmful effects of excessive social networking site consumption may arise from its predominantly passive nature, while instant messaging tools, which primarily involve active engagement, do not exhibit this detrimental impact.
Keywords: L82; D91; I12; I31; 330; Loneliness; mental well-being; social media use; Europe